The effect of Al, Si and Fe contents (selective dissolution) on soil physical properties at the northern slope of Mt. Kawi - I Nita; S R Utami; Z Kusuma (Brawijaya University, 2015)
A toposequence at the northern slope of Mt. Kawi (East Java), having andic properties, were studied. Soil samples at various horizons from five profiles along the toposequence were selected for this study. Selective dissolution analyses (oxalate acid, pyrophosphate and dithionite citrate extractions) were performed to predict the amorphous materials, as reflected from the extracted Si, Al, and Fe. The contents of these three constituents were then correlated to the soil physical properties. The andic characters were indicated by low bulk density (0.43-0.88 g/cm3) and considerable amounts of Alo (1.3-4.2%) and Feo (0.6-2%), which tended to increase with depth. As a consequence, high content of total pores (>70%) and water content at pF 0, 2.54, and 4, as well as strong aggregate stability were detected (MWD of 2.4-4.5 mm and 1.4-4.5 mm, respectively, in Andisols and Non-Andisols). Water content at pF 0, 2.54, and 4, were significantly affected by respectively %Sio, % Fed, % Fep, and % Fed. However, bulk density was closely related to %Ald only.